REASEARCH TO PROPOSE SOME TECHNOLOGICAL PARAMETERS WHEN SLICING Betula alnoides WOOD - Tien Duong, Hoang (Journal of Forestry Science and Technology, 2020)
The article introduces research results in order to propose some reasonable technological parameters when slicing Betula anoides wood by VS-10 slicing machine manufactured by Taiwan, with two criteria are high quality and low cost. The research variables selected are the cutting speed of the slicing machine and the sloping angle of the slicing knife. The selected research parameters are surface roughness, frequency of crack and power cost of the machine. The research process is carried out by experimental methods, the achieved results are as follows: The number of repetitions needed during the experimental study of Betula anoides wood sliced ​​by VS-10 machine was 6 times. Correlation equation between cutting speed and power cost, surface roughness: N = 0.09 V + 0.081; Hmax = -71 V + 258.99. Correlation equation between sloping angle of the slicing knife with surface roughness and power cost of the machine: Hmax = 0.058 e2 – 3.857e + 141.771; N = 0.001 e + 0.277. Correlation equation between sloping angle of the slicing knife and cutting speed of the slicing machine with surface roughness and power cost of the machine: Hmax = 3.864 e - 1.618 eV + 89.001; N = - 0.005 e + 0.003 e V + 0.244. By solving the multi-objective optimization problem, two technological parameters were identified and proposed: The slicing speed is 3m/s, the sloping angle of the slicing knife is 20 degrees.